2014
DOI: 10.1016/j.appet.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Incubation of saccharin craving and within-session changes in responding for a cue previously associated with saccharin

Abstract: Time-dependent increases in cue-induced sucrose seeking after forced abstinence have been described in rats with a history of sucrose self-administration, suggesting sucrose craving “incubates”. In the present study, we examined whether the incubation of craving generalizes to the artificial sweetener, saccharin. Thirty-one male Long-Evans rats lever pressed for 0.3% saccharin solution 1 h/day for 10 days. On either Day 1 or 30 of forced abstinence, rats responded for 1 h for presentation of a tone + light cue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…36 This choice was validated, as the LPPs elicited by pleasant and unpleasant (relative to neutral) cues did not show a comparable trajectory, reflecting the specificity of our findings to drug-related cues. Overall, the current findings in individuals with cocaine use disorders are consistent with those of previous reports of heightened behavioral responding for drug-related cues with increasing duration of abstinence in animal models of addictions to cocaine, 4,37 heroin, 38 methamphetamine, 39 alcohol, 40 nicotine, 41 sucrose, 42 and saccharine, 43 with an eventual decline after a protracted period of abstinence. 5 …”
Section: Discussionsupporting
confidence: 90%
“…36 This choice was validated, as the LPPs elicited by pleasant and unpleasant (relative to neutral) cues did not show a comparable trajectory, reflecting the specificity of our findings to drug-related cues. Overall, the current findings in individuals with cocaine use disorders are consistent with those of previous reports of heightened behavioral responding for drug-related cues with increasing duration of abstinence in animal models of addictions to cocaine, 4,37 heroin, 38 methamphetamine, 39 alcohol, 40 nicotine, 41 sucrose, 42 and saccharine, 43 with an eventual decline after a protracted period of abstinence. 5 …”
Section: Discussionsupporting
confidence: 90%
“…Incubation of craving (Grimm, Hope, Wise, & Shaham, 2001) is described as an abstinence-dependent increase in responding for a cue associated with food or drug (Grimm et al, 2011) and, recently, has been reported with the non-food or drug reinforcer saccharin (Aoyama, Barnes, & Grimm, 2014). Incubation of craving has been observed in human addicts (Nava et al, 2006; Bedi et al, 2011; Wang et al, 2013; Li et al, 2014) and may be a key factor in high rates of relapse to drugs and food in humans.…”
Section: Discussionmentioning
confidence: 99%
“…This parameter represents the rate of response decrease produced by a single presentation of a reinforcer. As noted above, this equation has been fit to within-session responding for either primary (Aoyama, 1998) or secondary reinforcers (Aoyama et al 2014). Aoyama et al (2014) hypothesized that for seeking behavior (responding for secondary reinforcement) the y -axis intercept (parameter a ) may represent vigor of seeking behavior and that the slope (parameter b ) may indicate persistence of seeking behavior.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we investigated the within-session changes in saccharin or sucrose seeking in the absence of drug challenge (Aoyama et al 2014). We found that a linear equation that had been previously applied to the within-session changes in responding for primary reinforcers (e.g., food) could describe those for secondary reinforcers (i.e., saccharin or sucrose seeking, Aoyama et al).…”
Section: Introductionmentioning
confidence: 99%